PENERAPAN MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (MK3) DI INSTALASI GAWAT DARURAT RSU PKU MUHAMMADIYAH YOGYAKARTA - Rahayuningsih, Puji Winarni; Hariyono, Widodo (Jurnal Kesehatan Masyarakat (Journal of Public Health), 2011)
officers, which can cause transmission of diseases to theofficer. conditions that can reduce the hazards and accidents in work such as work that is organized, executed in accordance with procedures, workplace safety and cleanlinessassured, and adequate rest. accidents do not happen by itself, but usually occurs with a sudden and not planned or unexpected. emergency department is a service unit that provides services in hospital first in patients with the threat of death and disability that has a primary role to provide initial treatment of patients with a spectrum of diseases and injuries are more extensive. This study aims to determine how the image of the application of occupational safety and health management (K3) in the emergency department RSU PKU Muhammadiyah Yogyakarta. Method: This was qualitative descriptive research using non-experimental approach. This study provides an assessment of a material or object that is based on a criteria that has been there. qualitative descriptive study aimed to describe objectively existing reality that is expressed in words, sentences or pictures. Results: The results showed that health care emergency department personnel, the use of personal protective equipment, hazard or accident prevention, periodic health checks, and training of K3 in the emergency department are in accordance with manual operation of safety, fire, and disaster awareness RSU PKU Muhammadiyah in Yogyakarta in 2005. Conclusion: Health care workers have been conducted properly in accordance with established procedures RSU PKU Muhammadiyah Yogyakarta. Usage of personal protective equipment has been properly implemented by emergency department staff in accordance with the procedures set RSU PKU Myhammadiyah Yogyakarta. Hazards and accident prevention work has been carried out properly by emergency department personnel. Periodic medical examinations are in accordance with established procedures RSU PKU Muhammadiyah Yogyakarta. Health and safety training are not addressed in the implementation manual safety, fire, and disaster awareness but especially hospital emergency department has implemented well. Keywords: Implementation, Management, Safety and Occupational Health, Emergency.